Hyperglycemia as a risk factor for in-hospital mortality in myocardial infarction: Hiperglicemia como factor de riesgo de mortalidad hospitalaria en infarto de miocardio - Barrantes-Alarcon, Ciro (2024)
Introduction: Myocardial infarction continues with high mortality rates, from 4.6% to 13.1%. There are predictive risk stratification models, such as the Grace Score, which does not include glycemia as a variable. Patients hospitalized for myocardial infarction with hyperglycemia on admission may have higher mortality, in ST elevated and non-elevated infarcts. Objectives: The objective of this review is to identify and systematize the evidence on hyperglycemia on admission as a biomarker of mortality and heart failure in acute myocardial infarction. Materials and Methods: The search was carried out in the MEDLINE database including the MeSH terms hyperglycemia and hospital mortality or heart failure in myocardial infarction, selecting 12 articles. Results: Hospital mortality was calculated in 11 articles, in 9 of them a significant association was found between hyperglycemia and hospital mortality, both in the bivariate and multivariate analysis, and in 2 articles this association was not demonstrated. For in-hospital mortality, the results of 11 articles included in this review were synthesized. The frequency of occurrence of heart failure was determined in 11 articles, finding a higher frequency in 9 of them. For in-hospital mortality, the results of 11 articles included in this review were synthesized and analyzed, in 8 the analysis was performed in non-diabetics, obtaining OR: 4.15, IC 95% (2.853-6.035), in 3 for diabetics obtaining OR 2.365 IC 95% (1.778- 3,146) and in 6 for the total population finding OR 3,314 (2,910-3,774). Conclusions: Hyperglycemia on admission is associated with increased mortality and frequency of occurrence of heart failure during hospitalization for myocardial infarction, with evidence of moderate quality.